2012
DOI: 10.1038/bmt.2011.260
|View full text |Cite
|
Sign up to set email alerts
|

High-dose corticosteroids with or without etanercept for the treatment of idiopathic pneumonia syndrome after allo-SCT

Abstract: Idiopathic Pneumonia Syndrome (IPS) is a common complication after allo-SCT and results in high mortality rates. Conventional treatment for IPS typically includes supportive care and high-dose corticosteroids (CS). Data suggests that TNF-a is important in the pathogenesis of IPS and that the TNF-a inhibitor etanercept may be useful for IPS treatment. We performed a retrospective comparison of consecutive patients treated at our center for IPS with CS only from 1999 to 2003 (group 1, n ¼ 22) or CS plus etanerce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…Historically, early response and overall survival have been poor (<50%) when IPS was treated with systemic corticosteroids plus supportive care measures alone. In the past decade, significant improvements in day 28 survival (>70%) were reported in 2 limited institution studies combining etanercept with systemic corticosteroids [7,8]. In the current study, the day 28 response (67%) and survival (72%) noted in the corticosteroid (plus placebo) arm greatly exceeded historical reports using corticosteroids as primary management (Table 6), whereas 1-year survival remained poor (16.7%).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Historically, early response and overall survival have been poor (<50%) when IPS was treated with systemic corticosteroids plus supportive care measures alone. In the past decade, significant improvements in day 28 survival (>70%) were reported in 2 limited institution studies combining etanercept with systemic corticosteroids [7,8]. In the current study, the day 28 response (67%) and survival (72%) noted in the corticosteroid (plus placebo) arm greatly exceeded historical reports using corticosteroids as primary management (Table 6), whereas 1-year survival remained poor (16.7%).…”
Section: Discussioncontrasting
confidence: 49%
“…More recently, the use of TNF inhibitors was proposed, with potential benefits noted in single or limited institution studies [7,8,14]. In particular, clinical trials combining a soluble TNF binding agent (etanercept [Enbrel], Amgen Inc., Thousand Oaks, CA) with systemic corticosteroids for the management of IPS reported high response rates and improved overall survival [7,8,14]. Etanercept is a soluble dimeric binding protein consisting of 2 soluble p75 TNF receptors fused to the Fc portion of a type I immunoglobulin molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Response rates of 18 to 30%, with day 28 survival < 50% have been reported when patients were treated with high dose corticosteroids and supportive care measures. [13, 20] In our current study, treatment with systemic corticosteroids and etanercept resulted in complete response rates of 71%, with day 28 survival 89% and 1-year survival 63%. Three other pediatric studies have confirmed that IPS remains an important complication in children, with cumulative incidence rates ranging from 6.7% – 11.8% post-HCT in children.…”
Section: Discussionmentioning
confidence: 51%
“…Recent, limited institution, clinical trials using a soluble, dimeric, TNFα binding protein (etanercept, Enbrel®; Amgen, Thousand Oaks, CA), when given in combination with systemic corticosteroids have noted significant improvements in response rate and early survival for patients with IPS. [3, 6, 20] In collaboration with the Pediatric Blood and Marrow Transplant Consortium (PBMTC) and Children’s Oncology Group (COG), we have conducted a multi-center, phase II trial to determine whether the addition of etanercept to standard treatment would improve outcomes for children with IPS.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] These laboratory insights led to clinical trials using TNF inhibition to treat IPS, which has demonstrated encouraging responses. [34][35][36] A large, prospective, phase 2 study combining etanercept with corticosteroids for children with IPS reported high early response rates and a 1-year survival of 63%, which is superior to all previous IPS reports. 36 A recent phase 3 trial of corticosteroids with or without etanercept, did not demonstrate definitive effects of TNF inhibition on response or survival of patients with IPS above steroids alone.…”
Section: Cd11bmentioning
confidence: 70%